The Widyatama Campus Environmental Planning Study refers to the Law of the Republic of Indonesia Number 26 of 2007 About Spatial Planning for Flood Discharge - Bambang Eko Widyanto; Asep Setiawan; Yanyan Agustian (Publikasi Indonesia, 2024)
Sustainable development in an area often causes land use changes that have a domino impact, especially in water resource management and flood discharge control. In the spirit of development, important aspects such as runoff management are often overlooked. This study aims to analyze the management of runoff water in the Widyatama campus area by referring to Law of the Republic of Indonesia Number 26 of 2007 concerning Spatial Planning. The research method uses secondary data in the form of rainfall from the Bandung Climatology Station and manual surveys for land use and topographic analysis. The results showed that the intensity of rain at the 2-year recurrence period (I2) was 127.56 mm. Rainfall intensity is also calculated for 5, 10, 20, 25, 50, and 100 year recurrences. Based on this analysis, land modification or innovation is needed, one of which is the construction of a detention pond that functions to restore the amount of flow to the river according to the zero run-off concept. With a study area of 3.61 Ha, a detention pond is needed for rainfall over 5 years with a storage capacity of 240 m³. The implementation of this innovation is expected to reduce flood risk and improve water management in the study area.